Dark matter in the Milky Way: uncertainties on its distribution and implications on its particle nature - Benito, Maria [UNESP] (2019)
The detailed knowledge of the dark matter (DM) distribution in the Milky Way (MW) is important for understanding the interplay between baryons and DM in the processes involved in galaxy formation and evolution. It is further a key element for experiments that aim to directly or indirectly detect the DM particle due to theoretically predicted non-negligible, weak interactions between DM and Standard Model particles. In this thesis, we aim to determine the distribution of DM in our Galaxy. First, we constrain the density profile of the DM halo by means of kinematical tracers of the total gravitational potential. We use objects in circular orbits around the Galactic centre (GC) as tracers of the total dynamical mass. By subtracting from the observed rotation velocities the velocities predicted for the visible component of the Galaxy (stars plus gas) -under the assumption of Newtonian gravity- we derive constraints on the DM distribution in the MW once a given parameterisation for the DM density profile is adopted. For the distribution of the visible, baryonic component of the Galaxy, we adopt a large array of observationally inferred, three-dimensional density profiles. In this way, we bracket current uncertainties on the shape and the normalisation of the Galactic visible component. Our determination of the DM density profile in the MW proceeds from astrophysical observations. These observations have sizeable uncertainties that need to be properly taken into account. We further present a full data-driven analysis that quantifies astrophysical uncertainties that affect the determination of the DM distribution in the MW, and therefore, the interpretation of results from direct and indirect DM particle searches. Furthermore, we study the DM distribution in the inner 2 kpc of the Galaxy. The inner Galactic region is dynamically dominated by baryons, and it is at the centre of a long-standing debate on whether the DM profile in the inner regions of galaxies is core or cusp. In our analysis, we adopt an estimate of the total dynamical mass within the inner 2 kpc of the MW. By simply subtracting from the total mass the stellar mass within the region under study, we infer the corresponding DM mass. We further study how this allowed DM mass translates into the parameter space of a particular parameterisation for the DM density profile. Finally, we present a methodology based on kinematical tracers of the total gravitational potential of the Galaxy that can be used for testing modified gravity theories at the scale of spiral galaxies.